Investigation of the structural transformation behavior of Ge2Sb2Te5 thin films using high resolution electron microscopy - Kim, Eun Tae; Lee, Jeong Yong; Kim, Yong Tae (AMER INST PHYSICS, 2007)
Structural transformation of the Ge2Sb2Te5 was investigated by a high resolution transmission electron microscopy (HRTEM). It was found that Ge atoms undergo umbrella-flip motion from a tetrahedral site into an octahedral site in transforming from the amorphous to the metastable phase of Ge2Sb2Te5. The presence of a twin boundary between fcc and hexagonal structured Ge2Sb2Te5 was also confirmed through the HRTEM observations. These results support the umbrella-flip model proposed by Kolobov [Nat. Mater. 3, 703 (2004)] and the epitaxial growth model proposed by Park [Appl. Surf. Sci. 256, 8102 (2006)]. (c) 2007 American Institute of Physics.
Keywords: CRYSTAL-STRUCTURE